Curricular articulation in higher education: an experience in initial teacher education - Aguiar, Ana Raquel (2022)
Curricular Articulation (CA) is undoubtedly a fundamental practice in the teaching-learning process. On the one hand, the construction of effective and solid knowledge implies holistic approaches at the level of disciplinary contents; on the other hand, it also implies a transversal intervention regarding the skills and abilities to be developed by students. Therefore, we advocate for a dynamic curricular conception in an integrative perspective to enable the promotion of significant learning. Based on these assumptions, this text is the result of an experiment conducted with 3rd year Basic Education students in a Polytechnic Institute in the North of Portugal in the academic year of 2019/2020. In this period, CA was carried out in two Curricular Units: one in the field of Portuguese Didactics, and the other one under internship conditions in Initiation to Professional Practice 3. By analyzing the study cycle, it is clear that there are contact points in terms of skills and content in this training process, which explains this experiment. Furthermore, the interconnection of knowledge, which will influence the students’ pedagogical practices in the future by providing them with experiences, is also considered fundamental. In methodological terms, this is an exploratory study, since it is the first experiment in this Curricular Unit involving both students and teachers. The results allow one to conclude that CA is seen in a very positive light by students, and it is undeniably an experience to be repeated by teachers. Students highlight the possibility of carrying out tasks, evaluative and reflective moments mutual to both Curricular Units, which allow them to articulate learning. In this sense, they consider the mobilization of knowledge, capacities, and skills relevant to both areas of utmost importance. They also highlight the use of certain resources which, built within the scope of one Curricular Unit, are (re)adapted in the light of the other, therefore enabling constant reorganization processes of high significance for future education professionals. In the same way, they also mention the development of significant learning which contributes to the construction of knowledge they consider fundamental. Furthermore, they consider this articulation to be necessary, as it allows them to experience model situations that can be mobilized for their future practice. The teachers mention the collaborative work involved as a strong point, namely in the planning of lessons and in the structuring of resources, highlighting the possibility of (re)building knowledge together.